2020
DOI: 10.1161/jaha.120.015794
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Cardiac Output: Accuracy and Precision of the Closed‐Circuit Acetylene Rebreathing Technique for Cardiac Output Measurement

Abstract: Background Accurate assessment of cardiac output is critical to the diagnosis and management of various cardiac disease states; however, clinical standards of direct Fick and thermodilution are invasive. Noninvasive alternatives, such as closed‐circuit acetylene (C 2 H 2 ) rebreathing, warrant validation. Methods and Results We analyzed 10 clinical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…The "gold standard" methods for determining cardiac output (Q) are the direct Fick and thermodilution techniques (1). Both are highly technical and very invasive, requiring arterial catheterization.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The "gold standard" methods for determining cardiac output (Q) are the direct Fick and thermodilution techniques (1). Both are highly technical and very invasive, requiring arterial catheterization.…”
Section: Background and Rationalementioning
confidence: 99%
“…Photoacoustic gas analyzers monitor the expired air and measure the disappearance rate of the blood soluble gas relative to the blood insoluble gas over the course of the rebreathing period to estimate Q. IGR-derived Q using the Innocor correlates well with the direct Fick (r=0.95) and thermodilution (r=0.94) methods during maximal exercise (3,4). A recent review comprising 10 clinical studies found that the correlation between IGR and the Fick method was higher than the correlation between the thermodilution and Fick method during submaximal steady state exercise (IGR vs Fick: r=0.84 [95% CI 0.74-0.90]; thermodilution vs Fick: r=0.73 [95% CI 0.61-0.82]), and that IGR demonstrated good Bland-Altman Limits of Agreement with the Fick method (1). Moreover, IGR had a higher reliability than the thermodilution method (IGR typical error…”
Section: Background and Rationalementioning
confidence: 99%
“…Peak V̇O 2 was defined as the highest oxygen uptake measured from at least a 30 s Douglas bag collection. Q̇c was measured using a modified acetylene rebreathing technique that is validated, reproducible, and equivalent to invasive measures of Q̇c during maximal exercise (Hardin et al, 2020 ). Arterial–venous oxygen difference (a‐vO 2 difference) was calculated from the ratio between Q̇c and oxygen uptake using the Fick Equation (Hearon Jr. et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…C 2 H 2 is an inert, soluble gas that enters the blood stream via pulmonary diffusion but does not bind to hemoglobin. Therefore, the disappearance rate of C 2 H 2 is proportional to pulmonary blood flow and in participants without lung disease, the pulmonary blood flow is equal to systemic blood flow ( Hardin et al, 2020 ). Stroke volume (SV) was then determined via continuously monitored heart rate (HR).…”
Section: Methods Assumptions and Proceduresmentioning
confidence: 99%